IMPLEMENTASI KEGIATAN EKSTRAKULIKULER ROHIS DALAM PEMBINAAN AKHLAK SISWA DI MADRASAH ALIYAH MUHAMMADIYAH 13 SEI RAMPAH KABUPATEN SERDANG BEDAGAI - Salahuddin Salahuddin (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This thesis examines the efforts made by extracurricular coaches in the guidance of morals of students in Madrasah Aliyah Muhammadiyah 13 Sei Rampah. The problems discussed in this thesis include the form of extracurricular activities of Spiritual Islam (ROHIS) held in Madrasah Aliyah Muhammadiyah 13 Sei Rampah, an effort made by the extracurricular activity builder ROHIS in fostering the noble character of learners in Madrasah Aliyah Muhammadiyah 13 Sei Rampah and factors Supporters and inhibitors of extracurricular activities of PAI in Madrasah Aliyah Muhammadiyah 13 Sei Rampah. Sources of data obtained are Head of madrasah, Deputy Head Madrasah, builder extracurricular activities ROHIS head of Administration and learners. Date collected and then processed through three stages of data reduction, date display, and data verification, and then drawn conclusions and analyzed qualitatively. The efforts of the extracurricular activities facilitators in the development of learners include efforts to instill and evoke religious beliefs, instill good social ethics in the family environment, community environment and school environment and inculcate good habits in the form of discipline, responsibility, social relations and perform ritual worship. a). The implications of this research are: To describe the objective condition of ROHIS extracurricular activity program in Madrasah Aliyah Muhammadiyah 13 Sei Rampah. b). To describe and analyze the effort of the extracurricular activity of ROHIS in the guidance of morality of students in Madrasah Aliyah Muhammadiyah 13 Sei Rampah. c). To identify and analyze the supporting and inhibiting factors of ROHIS extracurricular activities in Madrasah Aliyah Muhammadiyah 13 Sei Rampah. This study is expected to contribute thoughts on the development of extracurricular activities ROHIS and noble character development for learners. In addition, this study is expected to be a reference and comparison for researchers who conduct similar research. This research is expected to provide constructive educational information to be considered for the school, community and government and related parties in an effort to improve the moral character of learners through extracurricular activities ROHIS